2004
DOI: 10.1657/1523-0430(2004)036[0128:siiasv]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Snowmelt Infiltration into Alpine Soils Visualized by Dye Tracer Technique

Abstract: Snowmelt infiltration into alpine soils can be severely reduced and even impeded by soil frost. In order to learn more about the true nature of infiltration pathways into alpine soils, dye tracer experiments were set up at 2 locations in southern Switzerland: at Hannigalp (2100 m) and at Gd St Bernard. Over the course of two winters (2000-2001 and 2001-2002) we excavated vertical soil profiles during snowmelt to examine the distribution of a dye tracer (Brilliant Blue FCF) that had been applied on the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 15 publications
1
32
2
Order By: Relevance
“…After that date the soil temperature stayed close to the freezing point. As shown by a nearby dye tracer experiment (Stähli et al, 2004), the soil remained frozen over the entire profile until the end of the snowmelt period. This tracer experiment allowed us also to detect an approximately 3 cm-thick basal ice sheet.…”
Section: Winter 2001/2002: Hannigalpmentioning
confidence: 95%
“…After that date the soil temperature stayed close to the freezing point. As shown by a nearby dye tracer experiment (Stähli et al, 2004), the soil remained frozen over the entire profile until the end of the snowmelt period. This tracer experiment allowed us also to detect an approximately 3 cm-thick basal ice sheet.…”
Section: Winter 2001/2002: Hannigalpmentioning
confidence: 95%
“…The digital images (Figure 7.5) were processed with the following method (details in Stähli et al 2004). The average level of the color channels was standardized to a reference common for all profiles.…”
Section: Local Scale Measurementsmentioning
confidence: 99%
“…Lindstrom et al (2002) also concluded that there were no clear effects of frozen soil on the timing and magnitude of runoff from an analysis of 16-yr data in a 0.5-km 2 watershed in northern Sweden. Researchers (Stadler et al 1997;Stähli et al 1999;Nyberg et al 2001) have demonstrated that soil structure, air-filled porosity, ice content, and the number of freezing and thawing cycles are the governing factors affecting the infiltration capacity of frozen soil. Even at very local scales, recent laboratory and field studies using dye tracer techniques (Flury et al 1994;Stadler et al 2000;Stähli et al 2004) revealed that water can infiltrate into deeper soil through preferential pathways where air-filled macropores exist at the time of freezing.…”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional numerical models using the fully coupled heat and mass balance equations (Flerchinger and Saxton 1989;Zhao and Gray 1997;Cox et al 1999;Koren et al 1999;Stähli et al 2001;Cherkauer and Lettenmaier 2003;Hansson et al 2004) showed a variety of ways to parameterize the hydraulic properties of frozen soil. Most of these models introduced the concept of supercooled soil water, which is the liquid water that coexists with ice over a wide range of temperatures below 0°C, by applying the freezing-point depression equation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation